Randomized placebo controlled clinical trial of an enteric coated micro‐pelleted formulation of a pancreatic enzyme supplement in dogs with exocrine pancreatic insufficiency - Parambeth, Joseph Cyrus (J Vet Intern Med, 2018)
BACKGROUND: Pancreatic enzyme supplements for the treatment of exocrine pancreatic insufficiency (EPI) in dogs can be uncoated or enteric coated. Enteric coated supplements might be advantageous. HYPOTHESIS/OBJECTIVES: Enteric coated enzyme supplements are superior to uncoated supplements in dogs with clinical EPI. ANIMALS: Eleven dogs with naturally occurring EPI that were apparently free from other diseases. METHODS: Randomized, blinded, controlled cross‐over clinical trial comparing a novel micro‐encapsulated enteric coated enzyme supplement to a commercially available uncoated product in dogs with clinical EPI. Search of serum canine serum trypsin‐like immunoreactivity concentration ≤ 2.5 µg/L in the Gastrointestinal Laboratory database was used to identify dogs with EPI. RESULTS: There was no difference −4.46% (95% CI: −7.97%‐–0.96%; P = .15) in the % acid hydrolysis fecal fat (primary outcome) between the enteric coated formulation (median: 11.8%; range 6.4%‐17.0%) and the uncoated pancreatic enzyme replacement product (median: 17.5%; range: 5.2%‐24.9%) in the 11 dogs that completed the study. Other variables did not differ between treatments. CONCLUSIONS AND CLINICAL IMPORTANCE: This study, which had low statistical power, did not detect a difference between formulations.